(3ZhGU GdHMGQs - (3OQhjT eMeO Hf CMeO GdQhei GdMfajs; (3EHQGgje GdMdHj , HQgGf GdOjf EHQGgje Hf eMeO Hf EHQGgje GdMdHj,J (B956 (3g` s ((3eMeO Hf YHO GdQMje s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOhQ GdYGdejf HGdYQaGf haQY dge ESJfHGW GdCMcGe s
(3BNQgG (B:s
(3JeJ GdcJGH HYhf Gddg Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3edJbi GdCHMQ GfXQ cTa GdXfhf L(B2 (3U` (B1814 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B66 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B80s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B151s
Keywords: (3Gdabg GdMfajs